KRAS Inhibitors in Lung Cancer: Current Strategies and Future Approaches (Canadian Oncology Today, 2024)
RAS (rat sarcoma viral oncogene homolog) proteins were among the earliest identified proteins that regulate cell growth, differentiation, and survival. The seminal work of Harvey and Kirsten in the 1960s paved the way for discovering these proteins that are encoded by retroviral oncogenes initially observed in rat sarcoma viruses. Among the different RAS proteins discovered to date, the KRAS (Kirsten Rat Sarcoma viral oncogene) isoform is the most frequently mutated in human cancers, occurring in 75% to 80% of cancers, followed by neuroblastoma RAS (NRAS), occurring in 12%, and Harvey RAS (HRAS), occurring in 3% of RAS cancers. KRAS, together with Epidermal Growth Factor (EGFR) and Anaplastic Lymphoma Kinase (ALK), are the most commonly identified oncoproteins, with known mutations in non-small cell lung cancer (NSCLC), and have been the focus of many research studies over the years. Despite significant success in targeting both EGFR and ALK mutations in NSCLC, more progress has yet to be made in developing therapies for KRAS mutations.